Balloon dilatation angioplasty of stenosed systemic-pulmonary artery shunts - Saltık, İrfan Levent; Eroğlu, Ayşe Güler; Öztunç, Funda; Sarıoğlu, Ayşe (The Turkish Journal of Pediatrics, 2000)
Seven children and an adult patient with cyanotic congenital heart defects underwent balloon dilatation angioplasty (BDA) of a stenosed systemic-pulmonary artery shunt to improve arterial oxygen saturation. We attempted to perform BDA using the transvenous route in all patients in whom the aorta connected with the right ventricle, such as in tetralogy of Fallot or double outlet right ventricle, in an effort to avoid femoral artery injury. We could use the transvenous route (antegrade) in three children with tetralogy of Fallot and in one child with tetralogy of Fallot and pulmonary atresia (one of them was 6.6 kg). Following BDA, there was an increase in arterial oxygen saturation from a mean of 65.9 ± 12.8% to a mean of 78.1 ± 8.3% (p < 0.05). On follow-up three to 37 months (mean 16.5 ± 11.2 months) after BDA, the condition of all patients had improved. Pulmonary hypertension developed in one patient during the follow-up period. It is concluded that BDA of stenosed systemic-pulmonary artery shunts is reasonable, effective and safe. Use of the transvenous route, if possible, to perform balloon dilatation angioplasty facilitates the safe advancement of the larger balloons in low-weight children.
Keywords: balloon dilatation angioplasty; systemic-pulmonary artery shunts; Blalock-Taussig shunts